Development of a two-stage biomass combustion system for reducing the emission pollutant - Surjosatyo, Adi; Ani, Farid Nasir (Penerbit UTM Press, 2002)
One of the most popular technological processes of converting biomass to a more useful energy is through direct combustion of biomass or gasification in a two stage combustion system. This combustion system configuration comprises of gasifier, gas ejector, cyclonic chamber and swirl burner, which are enclosed by the circular chamber. A series of tests were carried out to investigate the effect of each device in contributing to the reduction of gas emission. The results show that the staged combustion method, including the installation of gas ejector, cyclone chamber and swirl burner in the current gasifier system has shown as significant device to reduce the CO concentration as well as NOx reduction.